Research of elastic-plastic deformation of the finned objects of finite size - Сизова, Наталья Дмитриевна (Technology audit and production reserves, 2016)
Finned conical and cylindrical bodies of finite size are used in many industrial processes such as the manufacture of pipes for various purposes, chambers of detonation presses et al., which are essential elements supported by different numbers of ribs with optimal geometrical parameters. This structure is subjected to stresses that lead to the appearance of elastic-plastic deformation, but it does not destroy it. To study the problem of determining the stress-strain state of finned cylindrical and conical bodies of finite size an approach based on the theory of small elastic-plastic deformations is proposed. The system of nonlinear equations is linearized using the method of variable elasticity parameters. Approximate solution of the linearized elastic problem on each the k-th iteration is constructed with use of the theory of R-functions into a single analytic expression. The solution of problems in this case allows to explore a wide class of technological elements without restrictions on the area form and loading types, find the allowable load value, which does not exceed the liquid limit, but greater than the elastic boundaries. Determination of the allowable load holds a saving of material resources and optimizes the geometric parameters of the design elements and predicts the optimal mode of operation of the assembly. Furthermore, it is possible to set the strength of the loaded structures, which are designed for continuous operation under load.